Penggunaan Media Konkret Tangram Pecahan untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas IV Sekolah Dasar - Martiani, Rita; Putra, Deni Adi; Martati, Badruli (Education Journal : Journal Educational Research and Development, 2026)
Critical thinking skills are essential competencies of the 21st century that need to be developed from the elementary school level. This study aims to: (1) Describe the use of concrete media of Fractional Tangram in improving students' critical thinking skills; (2) Analyze the improvement of students' critical thinking skills after the use of concrete media of Fractional Tangram. This research uses the design of Classroom Action Research (PTK) which is carried out in two cycles. The research subjects consisted of 28 grade IV students of SD Negeri Tambak Wedi 508 Surabaya. Data was collected through observation of the learning process using observation sheets and indicator-based critical thinking skills tests that included interpretation, analysis, evaluation, inference, explanation, and self-regulation. The data was analyzed quantitatively descriptively by calculating the average score and percentage of improvement, as well as qualitatively to describe the learning process. The results showed a significant improvement in both aspects studied. The observation score of the learning process increased from 1.9 (Less category) in Cycle I to 3.4 (Good category) in Cycle II. The critical thinking skills score increased from an average of 23.2 (Good category) to 31.0 (Very Good category) with an increase of 33.6%. All critical thinking indicators have increased, with the highest achievements in the aspects of self-regulation (1.4 points), analysis (1.4 points), and evaluation (1.4 points). Thus, it can be concluded that the concrete media of Fractional Tangram is effective in improving the critical thinking skills of grade IV elementary school students, both in terms of the learning process and learning outcomes.